How Workload, Discipline, and Work Stress Affect Employee Performance? - Gde Bayu Surya Parwita; Made Ika Prastyadewi; Ni Putu Putra Intan Cahyani; Ni Putu Ratih Indira Swari (Philippine Social Science Journal, 2025)
This study analyzes the impact of workload, work discipline, and work stress on employee performance at PT. (LLC) X Bali. Utilizing a census method with 57 respondents and multiple linear regression analysis, the findings demonstrate that while strong work discipline positively influences performance, high workload and work stress significantly hinder it. These results suggest that management should prioritize mitigating excessive workload and stress while maintaining disciplinary standards to enhance productivity. However, given the study's small sample size and cross-sectional nature, future research should expand to include additional variables—such as job satisfaction and organizational commitment—and broader demographics to improve generalizability.